STUDY OF FERTILIZER (ORGANIC + INORGANIC) FORMULATION TO IMPROVE GUBAL AGARWOOD FORMATION IN KETIMUNAN TREE (Gyrinops versteegii) - I Made Mega; A.A. Nyoman Supadma (International Journal of Biosciences and Biotechnology, 2018)
A study of fertilizer formulation (organic + inorganic) to increase the formation of sapwood (gubal) on agarwood plants (Gyrinops versteegii), had done to find the best fertilizer formulation that capable of increase and accelerate either growth and agarwood formation of sapwood on agarwood trees. The first year of study was conducted in Marga Tabanan Village. The field research was Randomized Block Designed (3 groups) with single factor of treatment. The tested treatment were 6 formulation of compound fertilizers and a control (unfertilized treatment). The compound fertlizers consisted of urea, SP-36, KCl, local compost, and dolomite in varying doses. The fertilizer formulations were applied on 21 agarwood trees that previously inoculated with mixed inoculant of Fusarium solani and Rhisopus sp. Three months after inoculation, the data from the following parameters were measured and statistically analyzed: plant height, stem circumference, sapwood weight, resin content and soil chemical properties.The results showed that the tested fertilizer compound had significant effect on plant height, sapwood weight, and resin rendement. No significant effect of fertilizer compound measured on the stem circumference. The highest sapwood weights was obtained on C treatment (14.39 g). The highest resin yield was obtained on B treatment (3.91%) which was relatively the same as that on C treatment (3.85%). Thus, the best fertilizer formulation for either plant growth, agarwood formation or agarwood resin was C treatment (100 g urea + 100 g SP-36 + 100 g KCl) + (7.5 kg compost) + (75 g Dolomite) per tree.